Enhancing UTAUT-2: Exploring Perceived Security and Innovativeness in Omnichannel Purchases of Essentials and F&B - Clara, Catharina; Sulastri, Sulastri; Maulana, Ahmad (Journal of International Conference Proceedings, 2024)
This study highlights the critical role of omnichannel platforms in transforming purchasing behavior, particularly for essential goods and food and beverage (FB) sectors requiring frequent engagement and seamless online-offline integration. By extending the UTAUT-2 model, this research incorporates Perceived Security and Personal Innovativeness as key factors to investigate omnichannel re-adoption. Using a quantitative survey of active omnichannel users in Indonesia, analyzed with PLS-SEM, the findings reveal a novel insight: traditional UTAUT-2 factors like Performance Expectation and Effort Expectation exert minimal influence, while Perceived Security and Personal Innovativeness significantly drive Behavioral Intention, which strongly predicts Usage Behavior. This underscores the importance of addressing security concerns and leveraging user innovativeness to enhance engagement with omnichannel systems. These results provide actionable insights for practitioners aiming to refine omnichannel strategies and contribute to the academic discourse by prioritizing novel determinants in consumer technology adoption. Future research should explore additional dimensions and address methodological constraints like cross-sectional design and sampling biases.